Interdisciplinary collaborative teaching in vascular surgery training: A randomized trial of radiologist-surgeon partnership in China - Xin Li; Wei Hu (PLoS ONE, 2026)
This randomized controlled trial evaluates an innovative interdisciplinary teaching model co-led by radiologists and vascular surgeons within China’s standardized residency training program. Forty trainees were randomized into two groups: one receiving collaborative teaching, which included joint lectures, radiologist-attended ward rounds, and interdisciplinary case conferences; and the other undergoing traditional vascular single-discipline training. The experimental group exhibited superior performance in CT interpretation accuracy (92.0% vs. 71.0%, P < 0.01), diagnostic accuracy (87.0% vs. 67.0%, P < 0.01), treatment plan rationality (mean 4.40 ± 0.75 vs. 3.65 ± 0.88, P < 0.01), and communication skills (median 43.00 vs. 33.00, P < 0.0001). These findings validate that structured interdisciplinary collaboration effectively bridges the gap between radiology and clinical practice, suggesting a paradigm shift in vascular surgical education.